2006
DOI: 10.1158/1078-0432.ccr-05-1864
|View full text |Cite
|
Sign up to set email alerts
|

Profiling markers of prognosis in colorectal cancer.

Abstract: Purpose: Colorectal cancer is one of the most common forms of cancer in developed nations and the incidence of this disease is increasing. There is a need to further stratify prognostically distinct groups of colorectal cancer, and the purpose of this study was to identify prognostically significant immunohistochemical marker profiles in colorectal cancer. Experimental Design: In this study, a range (n = 23) of markers [pRb, p16, p21, p27, p53, proliferating cell nuclear antigen, cyclin D1, bcl-2, epidermal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 39 publications
7
91
1
4
Order By: Relevance
“…In our study, patients with p53 expression had a better overall survival (p=0.048) which is in line with previous studies (9,22,23). These studies partly include large patient cohorts and long follow-up periods.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, patients with p53 expression had a better overall survival (p=0.048) which is in line with previous studies (9,22,23). These studies partly include large patient cohorts and long follow-up periods.…”
Section: Discussionsupporting
confidence: 93%
“…1A). Positive expression of p21 was defined as a nuclear staining reaction in >5% of the tumor cells according to other publications (9). We observed no p21 expression in 8 carcinomas, a nuclear expression in <5% of the tumor cells in 77 carcinomas and a nuclear expression in >5% in 31 colorectal carcinomas.…”
Section: Resultssupporting
confidence: 67%
“…In recent years, this statistical tool has been applied to analyze immunohistochemical results on Formalinfixed paraffin-embedded tissues using multiple antibodies, and has demonstrated that tumors clustered into groups that correlated to their site of origin, 23 phenotype, 24,25 biologic potential, 26 and prognosis. [27][28][29] Our goal was to identify a cluster of markers that can be used in combination in a diagnostic immunohistochemical panel for differentiating adenoid cystic carcinoma from polymorphous low-grade adenocarcinoma. In this study, 47 tumors were immunostained with primary antibodies against six proteins, and their expressions were subclassified into three categories (negative, focal, and diffuse expression), generating a dataset comprising of 846 (47 Â 6 Â 3) individual observations.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the molecular mechanisms that control CRC progression are related to the altered expression of different proto-oncogenes, tumor suppressor genes, cytokines and their receptors, including Ras, Src, p27 kip1 , p16 ink4a , interleukin (IL) and the epidermal growth factor receptor (EGFR). [1][2][3][4][5][6][7] Notably, these abnormalities involve the signal transducers and activators of transcription (STAT) signaling pathway, specifically STAT3 and STAT5 signaling, although very few studies have reported the abnormal expression or activation of STAT proteins in colorectal cancer. 8 Understanding the molecular mechanisms of STATs may further the development of novel therapies targeted in CRC treatment.…”
mentioning
confidence: 99%